Success Factors in Managing Wastewater Infrastructure through Community Participation (Case Study: Wastewater Infrastructure in Residential Areas of Medan Deli Subdistrict, Medan) - Hidayat, Rahmat; Milanie, Feby Milanie; Nuraini, Cut; Azhari, Ihsan; Sugiarto, Abdi (International Journal Papier Advance and Scientific Review, 2023)
Both central and local governments strive to implement sanitation programs, especially in the management of wastewater infrastructure, with a focus on community involvement from planning to maintenance. The Medan Deli Subdistrict, engaged in wastewater infrastructure management through community participation, faces challenges, including a decline in users and dysfunctional management groups. The limited community involvement also impacts the failure of management. The research was conducted in the Medan Deli Subdistrict using survey and exploration methods. The analysis of survey questionnaire data with the Relative Importance Index (RII) method identified five key success factors, used as research indicators to identify obstacles through structured interviews. The research results show that these factors involve the choice of technology, organization, and leadership, which have proven to have a significant impact. Additionally, service convenience, operator performance, and clean and healthy living habits also prove to be drivers of success in this management. In this context, it can be concluded that technical factors, especially the selection of technology and organization, dominate the success of wastewater management. The success of wastewater infrastructure development through community participation also heavily depends on institutional elements and social approaches. However, after identifying success elements, some analyzed obstacles include the process of selecting technology means that are not in line with the needs and preferences of the community, managers responsible for wastewater infrastructure management often relocating without replacement, hindering the administrative process of management, infrastructure maintenance requiring operators to routinely perform operational functions, and a community that is not fully committed to implementing clean water infrastructure management.